2017
DOI: 10.1002/humu.23224
|View full text |Cite
|
Sign up to set email alerts
|

AberrantHRAStranscript processing underlies a distinctive phenotype within the RASopathy clinical spectrum

Abstract: RASopathies are a group of rare, clinically related conditions affecting development and growth, and are caused by germline mutations in genes encoding signal transducers and modulators with a role in the RAS signaling network. These disorders share facial dysmorphia, short stature, variable cognitive deficits, skeletal and cardiac defects, and a variable predisposition to malignancies. Here, we report on a de novo 10-nucleotide-long deletion in HRAS (c.481_490delGGGACCCTCT, NM_176795.4; p.Leu163ProfsTer52, NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Consistent with the collected functional data, p.Gln72Leu (analogous to p.Gln61Leu in HRAS, NRAS, and KRAS) is a strong activating mutation and has not been observed to occur as a germline event in HRAS, KRAS, or NRAS. Similar differences in the biological and phenotypic consequences have previously been reported for HRAS, NRAS, and KRAS, [12][13][14]30,31,[46][47][48][49][50][51][52][53] including the positions corresponding to the presently identified RRAS2 mutations. The genotype-phenotype correlations in HRAS are illustrative and correlate well with the present findings: while p.Ala59Thr has been associated with Costello syndrome and p.Gly12Val has been reported with severe expression of Costello syndrome, 46 p.Gln61Leu and other changes at this codon have only been reported as somatic events in cancer (Table S1).…”
supporting
confidence: 82%
“…Consistent with the collected functional data, p.Gln72Leu (analogous to p.Gln61Leu in HRAS, NRAS, and KRAS) is a strong activating mutation and has not been observed to occur as a germline event in HRAS, KRAS, or NRAS. Similar differences in the biological and phenotypic consequences have previously been reported for HRAS, NRAS, and KRAS, [12][13][14]30,31,[46][47][48][49][50][51][52][53] including the positions corresponding to the presently identified RRAS2 mutations. The genotype-phenotype correlations in HRAS are illustrative and correlate well with the present findings: while p.Ala59Thr has been associated with Costello syndrome and p.Gly12Val has been reported with severe expression of Costello syndrome, 46 p.Gln61Leu and other changes at this codon have only been reported as somatic events in cancer (Table S1).…”
supporting
confidence: 82%
“…This finding further highlights the current need to optimize the bioinformatics workflow required to attain an accurate functional annotation of the large number of variants that are routinely identified by genome-wide sequencing, as well as the importance of not underestimating synonymous variations when screening for disease-causing variants (Gelfman et al, 2017;Livingstone et al, 2017;Pantaleoni et al, 2017).…”
Section: The Functional Impact Of Variants Was Analyzed By Combinedmentioning
confidence: 94%
“…It is now well‐established that synonymous variants may alter gene expression through modulation of splicing, mRNA stability, and translation, and disturbing these processes may contribute to human disease (Mueller, Larsen, Garibaldi, Hatfield, & Hertel, ; Supek, Minana, Valcarcel, Gabaldon, & Lehner, ). This finding further highlights the current need to optimize the bioinformatics workflow required to attain an accurate functional annotation of the large number of variants that are routinely identified by genome‐wide sequencing, as well as the importance of not underestimating synonymous variations when screening for disease‐causing variants (Gelfman et al, ; Livingstone et al, ; Pantaleoni et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Several rare G12 variants, including G12V, G12D, G12C and G12E, are associated with the development of a more-severe form of CS that is lethal in infancy ( Weaver et al, 2014 ). In addition to single-nucleotide variants, alterations that affect the splicing of HRAS ( Guil et al, 2003 ) have been reported in patients with CS ( Pantaleoni et al, 2017 ). Almost all reported cases of CS are de novo ( Rauen, 2007 ).…”
Section: Csmentioning
confidence: 99%